Total laparoscopic excision of pelvic retroperitoneal ganglioneuroma: a case report and review of the literature - Lan, Kangyun; Ding, Hongfan; Liu, Wenli; Tang, Hanmei; Chen, Guangyuan; Huang, Ping (Frontiers in Surgery, 2026)
Ganglioneuroma is defined as a rare, benign neurogenic tumor. This paper reports a case of pelvic retroperitoneal ganglioneuroma in a 12-year-old girl and reviews the relevant literature. The patient was found to have a pelvic retroperitoneal mass incidentally during a health check-up and had no significant clinical symptoms. Gynecological ultrasound revealed a hypoechoic mass posterior to the uterus, measuring approximately 63 × 52 mm, with clear boundaries. No obvious abnormalities were observed in the uterus and adnexa. Pelvic CT showed a well-defined, low-density mass measuring 59 mm × 55 mm with mild enhancement at the posterior margin, the adjacent coccygeal bone showed discontinuity and was closely related to the mass, the rectum was displaced anteriorly with clear demarcation from the mass, and no enlarged lymph nodes or effusion were found in the pelvis. The tumor was successfully and completely resected via laparoscopy, and pathological examination confirmed the diagnosis of ganglioneuroma. The standard surgical methods and approaches for retroperitoneal ganglioneuroma have not yet been established. The successful diagnosis and treatment of this case highlight the importance of accurate preoperative assessment and appropriate surgical planning. The literature review summarizes the clinical manifestations, diagnostic methods, and therapeutic strategies of ganglioneuroma, aiming to provide references for clinicians.